2022
DOI: 10.3389/fonc.2022.887977
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of tissue proteomics in patients with papillary thyroid microcarcinoma uncovers the underlying mechanism of lymph node metastasis and its significant sex disparities

Abstract: BackgroundLymph node metastasis (LNM) in papillary thyroid microcarcinoma (PTMC) is associated with an increased risk of recurrence and poor prognosis. Sex has been regarded as a critical risk factor for LNM. The present study aimed to investigate the molecular mechanisms underlying LNM and its significant sex disparities in PTMC development.MethodsA direct data-independent acquisition (DIA) proteomics approach was used to identify differentially expressed proteins (DEPs) in PTMC tumorous tissues with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In a tissue-based proteomic study, Cao et al compared papillary microcarcinoma tissues depending on metastases, although not specifying whether they were central or lateral, and found signi cant differences in differentially expressed proteins (DEP), namely downregulation of Solute Carrier Family 25 Member 15, DIRAS Family GTPase 2, Phospholipase A2 receptor 1 and Mitochondrial Amidoxime Reducing Component 1, while these DEPs were enriched in mitochondrial dysfunction, possibly promoting tumorigenesis by activating the PI3K/AKT signalling pathways. Interestingly, this research has also found signi cant differences in proteomic pro les depending on sex (71).…”
Section: Introductionmentioning
confidence: 56%
“…In a tissue-based proteomic study, Cao et al compared papillary microcarcinoma tissues depending on metastases, although not specifying whether they were central or lateral, and found signi cant differences in differentially expressed proteins (DEP), namely downregulation of Solute Carrier Family 25 Member 15, DIRAS Family GTPase 2, Phospholipase A2 receptor 1 and Mitochondrial Amidoxime Reducing Component 1, while these DEPs were enriched in mitochondrial dysfunction, possibly promoting tumorigenesis by activating the PI3K/AKT signalling pathways. Interestingly, this research has also found signi cant differences in proteomic pro les depending on sex (71).…”
Section: Introductionmentioning
confidence: 56%
“…Therefore, strong input emerging from this study concerns the need for efforts in the development of proteomic assays in thyroid cytological samples, rather than genomics, to detect mutated proteins that could promote metastasis. Proteins that characterize mitochondrial inner membrane, mitochondrial transport, cell respiration, and ribosomal activity have already been reported to be more expressed in tissues of PTMC with LNM than those without LNM [ 28 ]. Hence, it was hypothesized that mitochondrial dysfunction may promote tumor progression by activating oxidative phosphorylation and PI3K/AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was hypothesized that mitochondrial dysfunction may promote tumor progression by activating oxidative phosphorylation and PI3K/AKT signaling pathways. Furthermore, four proteins (i.e., SLC25A15, DIRAS2, PLA2R1, and MTARC1) associated with a TC poor prognosis have been recognized to be downregulated in PTMC with LNM; thus, they have been proposed as candidate biomarkers for predicting PTMC metastasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 signaling pathway facilitated aggressive and progressive metastatic PTC by rewriting the glucose/iodine metabolic program in hypoxia microenvironment [31] . In addition, MAPK is present in various signaling pathways and broadly known to be involved in LNM of PTC [32] . Another important signal pathway, PI3K/Akt, was also analyzed to be closely related to multiple KEGG pathways, which functioned to thyroid tumorigenesis and progression by enhancing protein synthesis and overall reprogramming of cancer cell metabolism [33][34] .…”
Section: Discussionmentioning
confidence: 99%